Factors associated with body weight status among adolescents in Labuan Federal Territory, Malaysia - Ho, Shu Fen (2020)
The prevalence of overweight and obesity among adolescents in developing countries are increasing including Malaysia. A cross-sectional study was conducted to determine socio-demographic characteristics, lifestyle factors, body image perception, family environment and built environment factors associated with body weight status (BMI for- age) among adolescents in Labuan Federal Territory, Malaysia. The study involved 481 secondary school Malaysian students aged 12-17 years. Information on socio-demographic characteristics, lifestyle, body image, family environment and built environment were collected using self-administered questionnaires. Body weight and height of the students were measured using standard procedures while BMI-for-age z-score (BAZ) was determined using WHO Growth Reference 2007. One day 24-hour dietary recall was obtained by face-to-face interview. The buffer analysis was conducted using Geographic Information System (GIS). A majority of the respondents were female (67.4%), Malays (55.0%), from rural schools (55.7%) and had achieved pubertal status (95.7%). The prevalence of overweight and obesity among the respondents was 33.1% (Males: 30.7%; Females: 34.3%), with mean BAZ of the respondents was 0.36±1.46 SD. A majority of the respondents skipped main meals (83.6%), skipped breakfast (68.6%) and snacked between meals (96.9%) daily. About half of the respondents skipped lunch (47.9%) and skipped dinner (49.8%). A total of 28.3% of respondents were at high risk of eating disorders. About three in four respondents were dissatisfied with their body size (73.3%). The mother’s mean BMI and father’s mean BMI were 26.5±5.6kg/m2 and 25.9±4.9kg/m2, respectively. A majority of the respondents did not have fast food outlets within the 500m (95.2%), 1000m (85.2%) and 1500m (79.0%) buffer of their homes. All respondents (100%) did not have fast food outlets within a 500m buffer of their schools. Bivariate analyses indicated that energy intake (r=0.274, p<0.001), higher frequency of eating outside home (r=0.145, p=0.038), not snacked morning tea (t=2.126, p=0.035), not snacked afternoon tea (t=2.414, p=0.017), not snacked supper (t=2.073, p=0.039), higher disordered eating score (r=0.212, p=0.002), dissatisfied body size (t=2.451, p=0.015), higher mother’s BMI (r=0.216, p=0.002), higher father’s BMI (r=0.249, p=0.001), less parental pressure to eat (r=-0.210, p=0.003), perceived higher parent weight (r=0.174, p=0.013), perceived higher teen weight (r=0.364, p<0.001) and were significantly associated with higher BMI-for-age of the respondents. Further, multiple linear regression indicated that being female (β=1.064), higher energy intake (β=0.409), higher disordered eating score (β=0.017), higher body size dissatisfaction (β=0.190), higher father’s BMI (β=0.052), less parental pressure to eat (β=−0.304) and perceived higher teen weight (β=1.020) significantly contributed towards higher BMI-for-age of the acceptable diet reporting respondents at p<0.05 level of significance explaining 41.1% of the variances in BMI-for-age (R2=0.411, F=19.545, p<0.001). The strongest factor of the BMI-for-age model was perceived teen weight (ΔR2 = 13.3%). In conclusion, the study found that being female, higher energy intake, higher disordered eating scores, higher body size dissatisfaction, higher father’s BMI, less parental pressure to eat and perceived higher teen weight contributed to higher BMI for- age of the adolescents in Labuan Federal Territory. Future healthy weight intervention may consider incorporating these identified factors to increase the effectiveness of the programmes.